Liquidity vs. Sustainability Dilemma: Do Loan Ratios Hinder Social Transparency in Banks of Emerging Asia-Pacific? - Borolla, Johanis Darwin; Muharam, Harjum; Pangestuti, Irene Rini Demi (Pusat P2M Politeknik Negeri Batam, 2025)
The aim of this study is to analyze the fundamental dilemma in banking concerning the trade-off between liquidity management and sustainability commitments, with a focus on the banking sector in emerging Asia-Pacific economies. The findings reveal that banks with higher Total Loans to Total Deposits (TLTD) ratios tend to exhibit stronger Social Disclosure Scores (SDS), driven by stricter regulatory oversight. In contrast, banks with higher Total Loans to Total Assets (TLTA) ratios demonstrate weaker sustainability disclosures, prioritizing financial performance over ESG commitments. This study highlights the crucial role of regulatory pressure in encouraging banks to improve ESG transparency, even when short-term financial gains are prioritized. The findings underscore the need for policymakers to develop regulatory frameworks that not only enforce sustainability disclosures for high-risk banks but also incentivize asset-heavy institutions to integrate ESG principles into their core financial strategies, ensuring a balanced approach to sustainability and financial stability.